The G2A Receptor Controls Polarization of Macrophage by Determining Their Localization Within the Inflamed Tissue - Kern, Katharina; Schäfer, Stephan M. G.; Cohnen, Jennifer; Pierre, Sandra; Osthues, Tabea; Tarighi, Neda; Hohmann, Stefan; Ferreiros, Nerea; Brüne, Bernhard; Weigert, Andreas; Geisslinger, Gerd; Sisignano, Marco; et al. (Frontiers in Immunology, 2018)
Macrophages are highly versatile cells, which acquire, depending on their microenvironment, pro- (M1-like) or antiinflammatory (M2-like) phenotypes. Here, we studied the role of the G-protein coupled receptor G2A (GPR132), in chemotactic migration and polarization of macrophages, using the zymosan-model of acute inflammation. G2A-deficient mice showed a reduced zymosan-induced thermal hyperalgesia, which was reversed after macrophage depletion. Fittingly, the number of M1-like macrophages was reduced in the inflamed tissue in G2A-deficient mice. However, G2A activation was not sufficient to promote M1-polarization in bone marrow-derived macrophages. While the number of monocyte-derived macrophages in the inflamed paw was not altered, G2A-deficient mice had less macrophages in the direct vicinity of the origin of inflammation, an area marked by the presence of zymosan, neutrophil accumulation and proinflammatory cytokines. Fittingly neutrophil efferocytosis was decreased in G2A-deficient mice and several lipids, which are released by neutrophils and promote G2A-mediated chemotaxis, were increased in the inflamed tissue. Taken together, G2A is necessary to position macrophages in the proinflammatory microenvironment surrounding the center of inflammation. In absence of G2A the macrophages are localized in an antiinflammatory microenvironment and macrophage polarization is shifted towards M2-like macrophages.